A Review of Long Distance Commuting Mines: Implications for Northern Mining Communities - Silvana Costa (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
In the last two decades, there have been nearly no new mining towns built in Canada. Governments and mining companies have viewed long distance commuting (LDC), commonly known as fly-in-flyout or fly-in mines, as a way to avoid problems associated with building a new community and providing for its sustainability after mine closure. LDC is also considered more cost-effective than building a mine town. The intensification of the use of LDC in the Canadian mining sector has been quite rapid, particularly in northern regions. However, LDC has implications to employees, their families and communities, which deserve further examination, particularly considering the significant expansion in Northern mining and Aboriginal participation in this sector. This paper presents a review of the major issues in long distance commuting, both from an industry and community perspectives. It is a result of preliminary investigation for a PhD research project that will be pursued by a Bridge Fellow and UBC Mining Sustainability Working Group member, and guided by an interdisciplinary research team at the University of British Columbia (UBC). The Bridge Fellowship Program is research-training program linking the UBC?s Faculties of Medicine, Engineering and Graduate Studies. Its mission is to develop creative evidence-based prevention measures for public, environmental and occupational health problems. The SWG is an interdisciplinary student group based in the UBC Department of Mining Engineering, committed to respond to the complex sustainability-related challenges currently faced by the mining industry. In other to pursue this project, it is paramount that industry and local communities alike participate in the development and clarification of research questions as well as in the research design. It is hoped that this paper will function as an invitation for industrial and community partners for such study. The main themes identified for this research are occupational health and safety of LDC employees, family life impacts and community health impacts of this model of resource development.